STRATEGI DIGITAL MARKETING DALAM MENINGKATKAN PENJUALAN PADA UMKM BERBASIS ONLINE - Arisandi, Edi; Setiawan, Rachmadi; Amalia, Fisy; Parinduri, Rizka Elvira; Munir, Abdul Razak (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to determine the effectiveness of digital marketing strategies in increasing sales in online-based MSMEs. This research approach collects data through a literature study, which involves reading literature from various sources including books, articles, journals, and reports using qualitative and deductive approaches. The results of this study indicate that digital marketing strategies are proven effective in increasing sales in online-based MSMEs. Some key strategies that can be implemented include utilizing social media as a promotional channel, optimizing marketplaces and websites, implementing content marketing, using paid digital advertising and search engine optimization (SEO), collaborating with influencers and affiliate marketing, customer relationship management (CRM), and data analysis and evaluation of digital marketing performance. The implementation of these strategies allows MSMEs to reach a wider range of consumers, build trust and loyalty, and increase sales sustainably with cost efficiency and appropriate data utilization.